Sliding mode control of a three-phase parallel active filter based on a two-level voltage converter - A. T. Boum; G. B. Djidjio Keubeng; L. Bitjoka (Systems Science & Control Engineering, 2017)
This paper presents the sliding mode control of a three-phase parallel active filter based on a two-level voltage converter to compensate for the harmonic currents of the pollutant loads. In order to calculate the reference harmonic currents, the p-q algorithm is used and the PWM is used to generate the control pulses of the inverter. Simulations in the Matlab-Simulink environment are provided to validate the theoretical study. The results obtained seem satisfactory in the harmonic compensation quality and the correction of the power factor. The selected comparison criteria are the transient regime and the Harmonic Distortion Rate in the line current.